Ability Tracking, School and Parental Effort, and Student Achievement: A Structural Model and Estimation - Fu, Chao; Mehta, Nirav (Journal of Labor Economics, 2018)
We develop and estimate an equilibrium model of ability tracking in which schools decide how to allocate students into ability tracks and choose track-specific teacher effort; parents choose effort in response. The model is estimated using Early Childhood Longitudinal Study data. Our model suggests that a counterfactual ban on tracking would benefit low-ability students but hurt high-ability students. Ignoring effort adjustments would significantly overstate the impacts. We then illustrate the trade-offs involved when considering policies that affect schools’ tracking decisions. Setting proficiency standards to maximize average achievement would lead schools to redistribute their inputs from low- to high-ability students.